Teaching teenagers with autism to seek assistance when lost. - Taylor, Bridget A (2004)
Three teenagers with autism were taught to respond to a vibrating pager to seek assistance in community settings when physically separated from their parents or teachers. A multiple baseline probe design across participants demonstrated that, upon being paged, participants successfully handed a communication card to a community member indicating that they were lost. Generalization was assessed in nontraining community sites and on outings with the participants' parents.